Romanticism and the uses of genre - Duff, David, 1962- (Oxford University Press, 2009)
This reappraisal of the role of genre in Romanticism explores the generic innovations that drove the Romantic 'revolution in literature'. Also examined is the movement's fascination with archaic forms such as the ballad, the sonnet, and the epic, the revival of which made Romanticism a 'retro' as well as a revolutionary movement.